Analisis Kebutuhan Bahan Ajar Digital Scrapbook untuk Meningkatkan Keterampilan Berpikir Kausalitas Siswa SMA N 1 Banuhampu - Muhammad Irsyad; Ridho Bayu Yefterson (Jurnal Kronologi, 2026)
The background of this research is the lack of variation in teaching materials and the reliance on traditional teaching methods, which affects the low causality thinking skills of students in schools. The aim of this research is to create digital teaching materials in the form of a scrapbook that can serve as a tool to improve students' causality thinking skills in history learning at SMA N 1 Banuhampu. This research uses a mixed-method approach with data collection techniques through observation, interviews, and reinforced by administering simple tests to students. In this way, the researcher can analyze the needs in developing digital scrapbook teaching materials. Based on these findings, the researcher found that there is a lack of variety in teaching materials, and many teachers and students still use conventional teaching materials during learning. Considering the problems that have been identified, the researcher plans to develop teaching materials utilizing technology. The use of technology will help create diverse learning styles that can be adapted and serve as support in enhancing students' causal thinking skills. The digital scrapbook teaching materials developed by the researcher in this study provide an opportunity for students to better understand the learning material, thereby improving their causal thinking skills in history learning.